From benzodithiophene to diethoxy-benzodithiophene covalent organic frameworks – structural investigations. Issue 23 (1st April 2016) - Lohse, Maria S.; Rotter, Julian M.; Margraf, Johannes T.; Werner, Veronika; Becker, Matthias; Herbert, Simon; Knochel, Paul; Clark, Timothy; Bein, Thomas; Medina, Dana D.
Abstract : The incorporation of side groups into a covalent organic framework (COF) backbone can be of significant importance for developing new frameworks with enhanced properties. Abstract : The incorporation of side groups into a covalent organic framework (COF) backbone can be of significant importance for developing new frameworks with enhanced properties. Here we present a novel π-stacked thiophene-based COF containing a benzodithiophene building unit modified with ethoxy side chains. The resulting BDT-OEt COF is a crystalline mesoporous material featuring high surface area and accessible hexagonal pores. We further synthesized a series of COFs containing both BDT and BDT-OEt building units at different ratios. The impact of the gradual incorporation of the BDT-OEt building units into the COF backbone on the crystallinity and porosity was investigated. Furthermore, molecular dynamic simulations shed light on the possible processes governing the COF assembly from molecular building blocks.